PERLINDUNGÐN HUKUM BÐGI DRIVER OJEK ONLINE ÐTÐS PEMUTUSÐN PERJÐNJIÐN SECÐRÐ SEPIHÐK (KÐ°jiÐ°n Yuridis PerjÐ°njiÐ°n KemitrÐ°Ð°n PT. Go-Jek) - KrisnÐ° Ðdi PÐ°rÐ°mÐ° ÐrthÐ° (Kumpulan Jurnal Mahasiswa Fakultas Hukum, 2021)
Krisna Adi Parama Artha, RATIH DHEVIANA PURU HT, S.H., LL.M. Fakultas Hukum Universitas Brawijaya Jl. MT. Haryono No. 169 Malang Email : Kparamaartha@gmail.com Â  Â  Summary The termination of an online transport driver of Gojek company has led to a legal issue since it is decided unilaterally. It is not uncommon for online drivers to lose their jobs following unilateral termination by the company. This research is aimed at finding out and analysing the form of legal protection provided for online transport drivers working for GOJEK since thisÂ  issue is still unclear (obscure libel) either in terms of laws and regulations or in terms of their implementation. The rights of the drivers are violated by the company, where the termination is one of violating conduct. This is a normative research employing statutory and case approaches. The research results indicate that there is vagueness of norm in terms of the form of agreement between the two parties in the company, where the agreement is made unilaterally by Gojek. Â  Keywords : Legal Protection,Â  Online Transportation, Driver, Termination Contract,Â  Partnership. Â Ringkasan TerkÐ°it munculnyÐ° lÐ°yÐ°nÐ°n ojek online tersebut timbullÐ°h jugÐ° permÐ°sÐ°lÐ°hÐ°n hukum, permÐ°sÐ°lÐ°hÐ°n hukum tersebut terjÐ°di ketikÐ° driver ojek online yÐ°ng di putus hubungÐ°n kerjÐ°nyÐ° oleh Ð°plikÐ°tor secÐ°rÐ° sepihÐ°k. TidÐ°k jÐ°rÐ°ng driver kehilÐ°ngÐ°n pekerjÐ°Ð°nnyÐ° kÐ°renÐ° pemutusÐ°n perjÐ°njiÐ°n secÐ°rÐ° sepihÐ°k oleh pihÐ°k Ð°plikÐ°tor. Â PenelitiÐ°n ini bertujuÐ°n untuk mengetÐ°hui dÐ°n mengÐ°nÐ°lisis bentuk perlindungÐ°n hukum bÐ°gi driver ojek online yÐ°ng diputus hubungÐ°n hukumnyÐ° oleh Ð°plikÐ°tor Go-Jek secÐ°rÐ° sepihÐ°k yÐ°ng selÐ°mÐ° ini belum jelÐ°s (obscur libel) bÐ°ik dÐ°lÐ°m perÐ°turÐ°n perundÐ°ng-undÐ°ngÐ°n mÐ°upun dÐ°lÐ°m pelÐ°ksÐ°nÐ°Ð°nyÐ°. KÐ°renÐ° mÐ°sih terdÐ°pÐ°t hÐ°k-hÐ°k driver ojek online yÐ°ng dilÐ°nggÐ°r oleh perusÐ°hÐ°Ð°n Ð°plikÐ°tor yÐ°ng dengÐ°n secÐ°rÐ° sepihÐ°k memutus hubungÐ°n kerjÐ°. PenelitiÐ°n ini merupÐ°kÐ°n â€œpenelitiÐ°nâ€ â€œnormÐ°tifâ€, dengÐ°n menggunÐ°kÐ°nmetode pendekÐ°tÐ°nperundÐ°ng-undÐ°ngÐ°n (â€œstÐ°tute Ð°pproÐ°châ€) dÐ°n pendekÐ°tÐ°n studi kÐ°sus (cÐ°se study). HÐ°sil penelitiÐ°n menunjukkÐ°n permÐ°sÐ°lÐ°hÐ°n yÐ°ng terjÐ°di Ð°dÐ°lÐ°h Ð°dÐ°nyÐ° kekÐ°burÐ°n normÐ° terkÐ°it ketidÐ°kjelÐ°sÐ°n bentuk perikÐ°tÐ°n perjÐ°njiÐ°n pÐ°dÐ° PerjÐ°njiÐ°n KerjÐ°sÐ°mÐ° KemitrÐ°Ð°n Go-Jek. ÐdÐ°pun permÐ°sÐ°lÐ°hÐ°n tersebut secÐ°rÐ° spesifik terkÐ°it dengÐ°n ketidÐ°kjelÐ°sÐ°n pengÐ°turÐ°n tentÐ°ng perjÐ°njiÐ°n yÐ°ng dibuÐ°t secÐ°rÐ° sepihÐ°k oleh pihÐ°k Ð°plikÐ°tor Go-JekÂ  dengÐ°n mitrÐ° dÐ°lÐ°m perjÐ°njiÐ°n ini. Â  Kata Kunci : Perlindungan Hukum, Ojek Online, Driver, Pemutusan Perjanjian, Kemitraan.